Clinical submission of supernumerary head of adducter brevis muscle - Vandana M,; Suri R,; Ravi S,; Vandana D,; Gayatri R, (Department of Surgery, UKM Medical Centre, 2011)
Adductor brevis is an important member of the adductor family occupying the medial compartment of the thigh executing the function of adduction and medial rotation. Deviations from normal anatomy are unusual and rarely reported. A survey of anatomical archives revealed occasional mention of additional bellies of adductor brevis muscle. The present study reports a double belly of adductor brevis muscle (AB) found during a cadaveric dissection class for medical students. The left sided AB displayed two bellies disposed in the same plane. This case report attempts to present the clinical applications of supernumerary bellies of this important adductor muscle of the thigh. It is feasible to categorize these muscular variations upon specialized radiological procedures such as CT and MRI scans only if the radiologist possesses satisfactory understanding of variant anatomy of this region. It is thereafter inferred that upon recognition these muscles present a fair chance of being of utilitised in reconstructions. A biomechanical overview of the present anomaly is also attempted